Ethnobotany of Bamboo in Sangirese, North Celebes - Alin Liana; Purnomo Purnomo; Issirep Sumardi; Budi Setiadi Daryono (Biosaintifika: Journal of Biology & Biology Education, 2017)
Advances in technology have encouraged the growth of a variety of biodiversity processing methods. These conditions encourage efforts to use natural resources more broadly. Ethnobotany can be used to document the local knowledge of the plants and their utilization. This study is aimed to describe the various forms of bamboo utilization by Sangirese. The method used was survey with purposive sampling. The data were analyzed descriptively based on exploration results and interviews with the people. The results showed there were 11 species of bamboo that are directly related to the life of local community in Sangirese, consisting of seven species of Bambusa, three species of Schizostachyum, and each one species of Dendrocalamus and Gigantochloa. Local community use bamboo for a variety of daily necessities; as building materials, handicraft, furniture, ceremonies, musical instruments, transportation, medicine, ornamental plants, as well as food. These exploration results are expected to complement the data of bamboo ethnobotany in Indonesia. Applicatively, this research is expected to be a reference in the national strategy of bamboo germplasm resource conservation.